Формування граматичної компетенції у студентів немовних спеціальностей ВНЗ у процесі вивчення англійської мови - Тригуб, Інна Петрівна (My University, 2014)
У статті розглядаються питання, що стосуються загальної характеристики граматичної компетенції; цілей її формування у студентів немовних спеціальностей ВНЗ; етапів формування граматичної компетенції; вправ для формування граматичної компетенції; дається характеристика засобів формування граматичної компетенції. The article is devoted to the problem of the grammatical competence formation. The general characteristics of grammatical competence are given; the aims of the grammatical competence formation are defined; the stages of the grammatical competence formation are given; examples of exercises for the formation of grammatical competence and short characteristics of means for the grammatical competence formation are given; the issue of the assessment of grammatical competence is specified.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; граматична компетенція; етапи; вправи; засоби; foreign grammatical competence; school grammatical minimum; exercises; means assessment of the foreign grammatical competence; stages